A palladium-catalyzed intramolecular carbonylative annulation reaction for the synthesis of 4, 5-fused tricyclic 2-quinolones. Issue 49 (26th May 2016) - Zhang, Xiwu; Liu, Haichao; Jia, Yanxing
Abstract : A new method for the synthesis of 4, 5-fused tricyclic 2-quinolones via a palladium-catalyzed intramolecular carbonylative annulation reaction is described. Abstract : A concise and efficient synthetic route to 4, 5-fused tricyclic 2-quinolones through the palladium-catalyzed carbonylative annulation of alkyne-tethered N -substituted o -iodoanilines has been developed. This reaction proceeds smoothly under mild reaction conditions and exhibits exceptional tolerance to a variety of functional groups. It has been successfully applied to the efficient synthesis of BI 224436, an HIV integrase inhibitor.